KONTROVERSI JFC (JEMBER FASHION CARNAVAL) KE-18 DALAM DISKURSUS MEDIA DAN PEMIKIRAN TOKOH AGAMA DI JEMBER - Bunga Surawijaya Ningsih (Indonesian Journal of Islamic Communication, 2020)
The 18th JFC (Jember Fashion Carnaval) in 2019 chose Cinta Laura Kiehl as its grand ambassador. The event, which is held in every year never escapes from the media spotlight. One of them happened in 2019. this event made by Dynand Fariz which is caused controversy among public and the mass media. This event invited polemics to the response of MUI Jember,the management of Muhammadiyah Jember, and the chief of FPI East Java since the clothes that is worn by cinta laura. this phenomenon, such as in media Bangsaonline.com and Potrerjember.com which are East Java media and online media that contain the most news about the 18th JFC controversy in 2019. In this study, researchers used William A. Gamson's framing analysis method and Andre Modiglani, which emphasized to the symbolic form through figurative and rhetoric which indirectly directs the news which forms an image from certain aspects in the public. In addition, it also contains of the views of religious leaders in Jember. The result was that Bangsaonline.com andotretjember.com looked shy when it reportes the controversy news. However, in the packaging of the news, words, terms, phrases, sentences, facts, paragraphs, and images used by online media tend to highlight images that indulge in genitals and violate religious values.